Manajemen Literasi Digital Dalam Pembelajaran Daring Di SD Negeri Margomulyo 2 Seyegan, Sleman, Yogyakarta - Haryanti, Winar; Mundilarno, Mundilarno (Media Manajemen Pendidikan, 2024)
The purpose of this study was to identify and describe digital literacy management in online learning at SD Negeri Margomulyo 2 Seyegan, to identify and describe the factors supporting and inhibiting digital literacy management in online learning at SD Negeri Margomulyo 2 Seyegan, and to find out and describe the results of management digital literacy in online learning at SD Negeri Margomulyo 2 Seyegan. This study uses qualitative research methods with observation, interviews, and documentation techniques. The analysis of this study uses the analysis of Miles and Huberman. This research reduces, presents, draws conclusions, and verifies the data. The results of the data analysis concluded that the principal of SD Negeri Margomulyo 2 Seyegan together with the teacher council had carried out the digital literacy management process in learning well, the supporting and inhibiting factors came from the internet network around the school which was less stable and parents of students, the results of the implementation digital literacy is that teachers are increasingly motivated to be more creative in providing learning and students become more enthusiastic in carrying out online learning.